Efficacy of PD-1-based immunotherapy after radiologic progression on targeted therapy in stage IV melanoma - Kreft, Sophia; Gesierich, Anja; Eigentler, Thomas; Franklin, Cindy; Valpione, Sara; Ugurel, Selma; Utikal, Jochen; Haferkamp, Sebastian; Blank, Christian; Larkin, James; Garbe, Claus; Schadendorf, Dirk; et al. (European journal of cancer, 2019)
Objectives - Targeted therapy (TT) is an effective treatment for advanced BRAFV600-mutated melanoma, but most patients eventually acquire resistance and progress. Here, we evaluated the outcome of second-line immune checkpoint blockade (ICB) after progression on dual BRAF and MEK inhibition. - Methods - Patients with metastatic melanoma progressing on combined BRAF + MEK inhibition and receiving second-line ICB between 2015 and 2019 in 9 tertiary referral centres were enrolled. Demographic and clinical data and blood counts of all patients were collected retrospectively. - Results - We identified 99 patients with stage IV melanoma receiving ICB (nivolumab, pembrolizumab [n = 39] or ipilimumab plus nivolumab [n = 60]) after progression on combined TT. The median progression-free survival was similar in the PD-1 and ipilimumab plus nivolumab group (2.6 months [95% confidence interval CI, 2.0-3.1] vs. 2.0 [95% CI, 1.4-2.6], p = 0.15). The objective response rate was 18.0% in the PD-1 and 15.0% in the ipilimumab plus nivolumab group (p = 0.70). The disease control rate was 25.7% for monotherapy and 18.3% for combined ICB (p = 0.39). The median overall survival was 8.4 months (95% CI, 5.1-11.7) for patients receiving PD-1 monotherapy and 7.2 months (95% CI, 5.2-9.1) for patients receiving ipilimumab plus nivolumab (p = 0.86). The latter was associated with a higher rate of treatment-related adverse events (AEs). No significant association of laboratory values or clinicopathological characteristics with response to second-line ICB was observed. - Conclusions - PD-1 monotherapy and combined ipilimumab plus nivolumab show similar activity and outcome in patients with melanoma resistant to BRAF + MEK inhibition. However, combined ipilimumab plus nivolumab was associated with a higher rate of treatment-related AEs compared with monotherapy.